2011
DOI: 10.4045/tidsskr.10.1417
|View full text |Cite
|
Sign up to set email alerts
|

Sakralnervestimulering

Abstract: SummaryBackground. Sacral nerve stimulation involves electrical stimulation of a sacral nerve root by means of an electrode and a stimulator. In the course of just a few years, sacral nerve stimulation has become a treatment option for selected patients with urinary retention, urinary incontinence, anal incontinence and constipation. The method is also being tested in connection with several other indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…However, an accurate and comprehensive evaluation is mandatory to improve the chance of successful response to treatment. Age is not a limitation, but its role is still controversial, as patients older than 65 years seem less likely to be eligible for SNM [26,32]; motivation, ability to handle the remote control and realistic expectations are other important factors to consider [32,33]. Psychiatric disorders and psychological factors had been advocated as predictors of failure, but recently this relationship has not been confirmed [26,31].…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an accurate and comprehensive evaluation is mandatory to improve the chance of successful response to treatment. Age is not a limitation, but its role is still controversial, as patients older than 65 years seem less likely to be eligible for SNM [26,32]; motivation, ability to handle the remote control and realistic expectations are other important factors to consider [32,33]. Psychiatric disorders and psychological factors had been advocated as predictors of failure, but recently this relationship has not been confirmed [26,31].…”
Section: General Considerationsmentioning
confidence: 99%
“…Patients suffering from neurological diseases such as MS, should be carefully evaluated and, although there is a lack of randomized controlled trials, SNM is usually offered if the course of the underlying neurological disorder can be considered stable or slowly progressive and patients are not likely to require repeated magnetic resonance scans [32,33]. In fact, it has been reported that loss of efficacy over time is a result of a new relapse [20,22,23].…”
Section: General Considerationsmentioning
confidence: 99%
“…The exact mechanism by which SNS works is not completely understood (6). The improved clinical outcome has been suggested to arise, as a result of the modulative effect that the electrical current delivered via the electrode exerts on the sacral nerve root and its corresponding neuromuscular components (1,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Sacral nerve stimulation (SNS) is a minimally invasive surgical technique that plays an important role in the treatment of disorders of the bladder and bowel (1). Over time the scope of conditions that SNS benefits has broadened; it was originally indicated in patients with urinary incontinence and non-obstructive urinary retention in 1981 (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation